Lingüística de corpus na análise do internetês - Gonzalez, Zeli Miranda Gutierrez (2007)
The study presented was motivated by the needs of comprehend the changes in the ortography of the Internet language, such as identify those changes frequency. The main aim of this study was to focus on the usage of a Corpus Linguistics approach for identification of frequent words most used in the studies corpus, such as frequences of changes in the ortography and the lexican gramathical standards of the internet language. There is a great range of studies on the internet language; however, very few of them has demontrated empirically how frequent changes are. Therefore, this study has tried to fill this gap by being able to show empirically the changes. The main theoretical underpinning for the research is provided by Corpus Linguistics, assuming the main notions presented by Biber (1998), Berber Sardinha (2004, 2006), Sinclair (1991,1996). For focusing the use frequency of lexican items it was considered, more specificly, the studies of Berber Sardinha (2000a, 2000b, 2004), Halliday (1991, 1992, 1993). Besides the Corpus Linguistics, the project also mentioned in questions such as: linguisctics diversity, genre, registry and internet language ortography along the perspective of Possenti (2006), Mollica (2007), Thurlow and Brown (2007), Crystal (2001), Othero, (2004). The corpus employed in the study was collected of young people s blogs that use internet for comunication. This corpus contains 135.021 tokes and 15.552 types. For the development of this research and of the analysis of the lexican items it was considered all the 500 most used words in the corpus studies. The frequences were used as base for decription of changes happened in the variant linguistics ortography the internet language. Among the most frequent items in the corpus was selected the td item with the sense of all, every, everything ( tudo, todo, toda, todas e todos in portuguese), with the objective of verify the standards lexican-gramathical, contributed for the respective senses. To sum up, this study hopes it has contributed to the study of the internet language, since there are few studies that have demosntrated empirically how these changes occur. This work also presentes the research limitations and its possible applications in the future